Individual and Social Level Factors Influencing Repeated Pregnancy among Unmarried Adolescent Mothers in Katavi Region-Tanzania: A Qualitative Study - Salim Juma Mpimbi; Mwajuma Mmbaga; Ziad El-Khatib; Minyahil Tadesse Boltena; Samwel Marco Tukay (MDPI AG, 2022)
Adolescents' pregnancy rates are still high in Tanzania, despite the efforts made by the national campaign. Within two years after the first pregnancy, adolescent mothers are more at risk of repeat conception. Repeated pregnancies are associated with increased maternal and perinatal outcomes. Katavi is a leading region in the country, with 45% adolescent pregnancy. Studies are scarce on factors influencing repeated pregnancy among unmarried adolescent mothers in the region. Therefore, this study explored the individual and social level factors influencing repeated pregnancy among unmarried adolescent mothers in the Katavi Region. An exploratory qualitative study, using key informant interviews (KIIs) was adopted for 16 participants. The study participants were unmarried adolescent mothers, aged 15-19 years, who were purposively sampled. Thematic analysis was used to analyze qualitative data. QSR Nvivo version 14 was used to analyze these data. The study established the individual factors influencing repeated pregnancy, which were inadequate sexuality knowledge, individually perceived barriers to contraceptive use, and the guarantee for marriage. Furthermore, the social factors identified were the power of decision-making, peer pressure, and the parent-child relationship. Inadequate education on sexuality is observed as a crucial factor influencing repeated pregnancy. Parents as primary educators should be encouraged to talk with their children, especially adolescent girls about sexual education.